Resilience in the supply chain management: Understanding critical aspects and how digital technologies can contribute to Brazilian companies in the COVID-19 context - Vitor William Batista Martins; Rosley Anholon; Walter Leal Filho; Osvaldo Luiz Gonçalves Quelhas (Modern Supply Chain Research and Applications, 2021)
Purpose - The present study aims to identify the most critical elements of resilience in the management of supply chains of Brazilian companies and, in the sequence, debate possible digital technologies mentioned by literature to enhance them. Design/methodology/approach - To identify the most critical elements, the information provided by qualified academics was used. Data analysis was performed through Cronbach's alpha coefficient, hierarchical cluster analysis and Fuzzy TOPSIS approach. Findings - Comparatively, the results pointed out three elements of resilience as the most critical in managing supply chains. They are the decision-making (understood as the definitions from the layout of the chain's operations network to the choice of warehouse locations, distribution centres and manufacturing facilities), human resources (understood as management for human resources development and knowledge management through training) and security (understood as issues related to information technology for data security). For each of them, bibliographic research was performed to identify technologies that enhance these elements of supply chain management resilience. Originality/value - The results presented here can significantly contribute to the expansion of debates associated with resilience in managing supply chains of Brazilian companies and directing researchers in the area.
Keywords: 650; Brazil; COVID-19 pandemic; Digital technologies; Resilience; Supply chain management